Convergence or Divergence: Preferences for Establishing an Unemployment Subsidy During the COVID-19 Period by Taxing Across Earnings Redistribution in Urban China - Zhou, Yaping; Zhou, Jiangjie; Li, Yinan; Rui, Donggen (Frontiers in Psychology, 2022)
With the advancement of marketization, China has achieved rapid economic growth and economic class differentiation. This research analyzes the data from China's livelihood survey, divides the urban Chinese into five socio-economic classes, and tests their preferences and tendencies for income redistribution. It obtains the general attitude differences in subsidy policy and income inequality during COVID-19. Our conclusions are consistent with the existing literature to a great extent; that is, personal factors (self-interest and belief in fairness) play a crucial role in the attitude of Chinese citizens. In the analysis of situational factors, the results show that the higher the level of marketization, the people are more likely to have stronger negative emotions about subsidy or redistribution policies. Further analysis shows that people with the lowest income are susceptible to the fact that income inequality has become significant and show a strong willingness to support the government's redistribution policy. In contrast, middle-class people tend to favour the government's redistribution policy, although they will not benefit much from the redistribution policy. Therefore, they lack the motivation to support the government in vigorously implementing the subsidy policy. Significantly, high-income people are indifferent, as they lack such motivation even more. The difference in redistribution preferences between upper-class and lower-class groups signals polarization in Chinese society, especially income redistribution.